Christian Religious Education for Children with Special Needs (Blind) at Slb-A Bartemeus Manado - Mokalu, Fini Syaloom; Supit, Sugijanti; Siang, Jhoni Lagun (International Journal of Education, Information Technology, and Others, 2024)
This research aims to develop a Christian Religious Education learning module that is accessible and effective for children with special needs who are blind. The research method used is research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The analysis stage was carried out to identify the needs and characteristics of blind students as well as the obstacles faced in learning Christian Religious Education. At the design stage, a module design is created that takes into account aspects of accessibility and is appropriate to students' conditions through the use of audio media and other assistive technology. The development process involved the creation and validation of modules by material, design and language experts and was based on recommendations and input from specialist blind education teachers. Implementation is carried out through module trials in special schools that serve blind children. Evaluation is carried out to assess the effectiveness of the module based on feedback from teachers and students, as well as through measuring increases in understanding and skills and achievement of grades. The research results show that the module developed can increase the understanding and participation of blind students in learning Christian Religious Education. This module is also considered practical and easy for teachers to use. Recommendations are given for improving the module and implementing it in special schools, especially for students with visual impairments in order to support inclusive and equitable Christian religious education for all children.